Penerapan Model Contekstual Teaching and Learning Berbasis Daring - Magfirah, Nurul; Thahir, Rahmatia; -, Anisa; -, Nurdiyanti; Wadji, Muhammad (BIO-EDU: Jurnal Pendidikan Biologi, 2021)
Improving learning outcomes can be done in various ways, one of which is by applying the right learning model, one of which is Contextual Teaching and Learning. Since the Covid 19 pandemic attacked the world, learning that was previously carried out offline has suddenly been carried out online by utilizing technology. Although online the Contextual Teaching and Learning model can be applied in online learning by utilizing media zoom meetings, google meetings, Google Classroom, and WhatsApp group. This research aims to determine whether there is an effect of the Contextual Teaching and Learning model carried out online on the learning outcomes of Biology students at Unisumuh Makassar. The method in this research is a type of quasi-experiment research with a pretest-posttest control group design research design. The population of this research was all students of biology Unismuh semester V and the sample in this study was 47 students, consisting of 25 people in the experimental group and 22 in the control group. The samples in this study were determined by using a random sampling technique. The results showed that the results of the data analysis of hypothesis testing using the t-test (independent-sample t-test) obtained a Sig value of 0.006 with a significance level (Î±) of 0.05, which indicates that the Sig value is smaller than the significance level (Î±). So the conclusion in this study is that there is an effect of the influence of the Contextual Teaching and Learning learning model applied in online learning on the learning outcomes of Biology students at Unismuh Makassar. Keywords: Learning Outcomes, CTL, Online Learning.